2018
DOI: 10.1111/pace.13463
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of electrical lead failures in patients referred for transvenous lead extraction procedures

Abstract: The most significant factors predisposing patients to ELF are the lead implantation approach and the presence of a cardioverter-defibrillator lead.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…In our study cohort, noninfectious indications were present in 81.7% of the patients. The observed low rate of TLE due to infection results from our strategy to rigorously treat pacing‐related complications and is consistent with our previous reports . The qualification for the TLE procedure was based on careful consideration with the patient whether to abandon or remove a lead and/or CIED .…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In our study cohort, noninfectious indications were present in 81.7% of the patients. The observed low rate of TLE due to infection results from our strategy to rigorously treat pacing‐related complications and is consistent with our previous reports . The qualification for the TLE procedure was based on careful consideration with the patient whether to abandon or remove a lead and/or CIED .…”
Section: Discussionsupporting
confidence: 87%
“…The observed low rate of TLE due to infection results from our strategy to rigorously treat pacing‐related complications and is consistent with our previous reports . The qualification for the TLE procedure was based on careful consideration with the patient whether to abandon or remove a lead and/or CIED . This process has been in line with the current expert consensus statement .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The observed low rate of TLE due to infection results from our strategy to rigorously treat pacing -related adverse events and is consistent with our previous report. 16 The decision whether or not to perform TLE was based on significant predictors of 30 -day mortality. In the multivariable analysis, only lower hemoglobin levels (OR, 1.642 per 1 g/dl), higher CCI (OR, 1.836 per 1 point), and the number of extracted leads at the index procedure (OR, 3.441 per 1 lead) remained significant.…”
Section: What's New?mentioning
confidence: 99%
“…[3,4] Importantly, ICD leads are prone to damage in long-term follow-up. [5,6] Kleemann et al demonstrated an increasing annual rate of failure among ICD leads during long-term follow-up, which reached 20% in 10-year-old ICD leads. [7] Increasing number of ICD lead implantations and significant risk of lead failure have resulted in growing need for TLE procedures involving ICD leads.…”
Section: Introductionmentioning
confidence: 99%